Crystal structure and EPR spectra of glycilglycilglycinocopper(II)bromide sesquihydrate - Castellano, Eduardo Ernesto (1998)
The title compound, Cu(glyglygly)Br·1·5H2O, crystallizes in the space group C2/c, with a = 21.468(7), b = 6.716(5), c = 16.166(6) A, β = 98.39°, and Z = 8. The tripeptide is bonded to one Cu(II) ion through the nitrogen [Cu–N=1.97(1)A] and oxygen [Cu–O=2.019(8)A] atoms of the amino end glycine residue and to another Cu(II) through one oxygen atom [Cu–O=1.931(9)A] of the terminal carboxyl group. This give rise to covalently bonded and infinite ···–Cu–tripeptide–Cu–··· chains. These chains are linked to one another by a network of H-bonds involving the water molecules and bromide ions. The Cu(II) ion is in a distorted tetragonal pyramidal coordination polyhedron. At the corner of the base of the pyramid are the terminal glycine nitrogen and oxygen atoms of one tripeptide, a carboxylic oxygen of another tripeptide and a bromide ion. The fivefold coordination is completed with a water molecule at the top of the pyramid [Cu–Ow=2.286(9)A]. For all orientations of the applied magnetic field the single crystal EPR spectra display a single anisotropic exchange collapsed resonance without hyperfine structure. Its position was measured in three perpendicular planes and the crystal g-tensor evaluated from the data. This tensor is interpreted in terms of the contributing Cu(II) complexes in the unit cell to deduce the principal values g1 = 2.273, g2 = 2.050 and g3 = 2.131 for the molecular gyromagnetic tensor. We also discuss the magnitude of the exchange interaction between neighboring copper ions in the lattice on the basis of the features in the EPR spectra and the structural information.